2011
DOI: 10.1007/s12229-011-9063-2
|View full text |Cite
|
Sign up to set email alerts
|

Flower Senescence-Strategies and Some Associated Events

Abstract: Different strategies of petal senescence and some important events associated with it have been discussed. On the basis of sensitivity to ethylene and associated symptoms of senescence, petal senescence has been classified into five different classes; besides changes in membrane permeability, autophagy and involvement of VPEs (Vacuolar processing enzymes), degradation of nucleic acids, protein turn over and remobilization of essential nutrients during petal senescence have been discussed. Nucleus appears to pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 216 publications
2
16
0
2
Order By: Relevance
“…A burst of endogenously produced ethylene in such flowers initiates senescence and coordinates the expression of genes required for the process [37]. In wintersweet, however, previous research indicated that no obvious production of ethylene could be detected from the flowers during flower development [38].…”
Section: Discussionmentioning
confidence: 99%
“…A burst of endogenously produced ethylene in such flowers initiates senescence and coordinates the expression of genes required for the process [37]. In wintersweet, however, previous research indicated that no obvious production of ethylene could be detected from the flowers during flower development [38].…”
Section: Discussionmentioning
confidence: 99%
“…Flower senescence is a highly regulated process that exhibits many of the structural, biochemical, and molecular changes that are hallmarks of programmed cell death. These include a loss of membrane permeability, increase in reactive oxygen species, and decreased levels of protective enzymes, followed by protein degradation, fatty acid breakdown, and degradation of nucleic acids (Wagstaff et al, 2002;Jones et al, 2005;Xu et al, 2006;Tripathi and Tuteja, 2007;Yamada et al, 2009;Shahri and Tahir, 2011;Rogers, 2013).…”
mentioning
confidence: 99%
“…Woltering and van Doorn (1988) investigated the role of ethylene in the senescence of petals by considering morphological and taxonomical relationships, and concluded that the ethylene sensitivity of plants is at the family level. Shahri and Tahir (2011) described flowers from the family Gentianaceae as ethylene insensitive (class 0), as like some other families, they show initial wilting during senescence. Some families showed low sensitivity (33 % effect, 1), or intermediate sensitivity (33-66 % effect, 2).…”
Section: Ethylene Sensitivitymentioning
confidence: 92%